(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
This article talks about the concept of smell and its linguistic expression. Through the concept of smell, it serves the purpose of the writer to differentiate and highlight the characters according to different signs. Verbalization of the concept of smell through linguistic means in a literary text is considered.